2020
DOI: 10.1678/rheology.48.207
|View full text |Cite
|
Sign up to set email alerts
|

Aspect Ratio of TEMPO-Oxidized Nanocellulose and Rheological Analysis of Aqueous Suspensions

Abstract: From dynamic light scattering (DLS) and small-angle X-ray scattering (SAXS) measurements, the aspect ratio f of twotypesofTEMPO-oxidizednanocellulose(TOCN)withdifferentfiberlengthswasquantitativelycalculated.Asaresult, the aspect ratios fofthenormallengthN-typeandtheshortfiberlengthS-typewere243and77,respectively.Rheologicalanalysiswascarriedoutinthedilutedtosemi-diluteconcentrationregionsoftwotypesofTOCNaqueoussuspensions.TheviscosityofsuspensionsincreasedlinearlywithTOCNconcentrationinthediluteregion,butin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Thus, even for the sample with 20 collisions (Vn = 32.7 %), it is suggested that the nanosized fibers 172 physically entangled to form a three-dimensional network structure. The storage modulus G' of the sample with 30 collisions (Vn = 47.4 %) was about 10 3 Pa, which was similar to that of the 1.5 wt% suspension of CNF (fiber length: 174 827 nm, aspect ratio: 243) prepared by the TEMPO oxidation (Yamagata 2020) and the 2 % suspension of 175 microfibrillated cellulose (MFC) prepared by high-pressure homogenization by Iotti et al (2011).…”
Section: Viscoelastic Behaviors Of Cnf Suspensionssupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, even for the sample with 20 collisions (Vn = 32.7 %), it is suggested that the nanosized fibers 172 physically entangled to form a three-dimensional network structure. The storage modulus G' of the sample with 30 collisions (Vn = 47.4 %) was about 10 3 Pa, which was similar to that of the 1.5 wt% suspension of CNF (fiber length: 174 827 nm, aspect ratio: 243) prepared by the TEMPO oxidation (Yamagata 2020) and the 2 % suspension of 175 microfibrillated cellulose (MFC) prepared by high-pressure homogenization by Iotti et al (2011).…”
Section: Viscoelastic Behaviors Of Cnf Suspensionssupporting
confidence: 52%
“…CNFs prepared from various types of cellulose sources using the above-mentioned process have been deployed in 80 various industries due to their value-added properties, and studies have been conducted focusing on the rheological properties of the CNF suspensions (Bercea and Navard 2000;Boluk et al 2011;Charani et al 2013;Iotti et al 2011;Iwamoto et al 2014;Naderi et al 2014;Pääkkö et al 2007;Tanaka et al 2020;Yamagata and Miyamoto 2021;Yamagata et al 2020). In other words, it is important to understand how to control the rheological behavior of the CNF suspensions in order to fully exploit the potential of the material.…”
mentioning
confidence: 99%
“…Average length of the S-CNC was estimated using Simha's formula (eq. A3) 20) , describing the relationship between p and [η] of ellipsoids, which were also used in several literature (Table I) 16,19,[21][22][23][24][25][26] . The average length was ~30 % longer than those determined by microscopy.…”
Section: Intrinsic Viscosity Of Nanocellulose Dispersionsmentioning
confidence: 99%
“…CNFs prepared from various types of cellulose sources using the above-mentioned process have been deployed in various industries due to their value-added properties, and studies have been conducted focusing on the rheological properties of the CNF suspensions (Bercea and Navard 2000;Boluk et al 2011;Charani et al 2013;Iotti et al 2011;Iwamoto et al 2014;Naderi et al 2014;Pääkkö et al 2007;Tanaka et al 2020;Yamagata and Miyamoto 2021;Yamagata et al 2020). In other words, it is important to understand how to control the rheological behavior of the CNF suspensions in order to fully exploit the potential of the material.…”
mentioning
confidence: 99%
“…Therefore, even if the shape and the length distribution of the fibers are the same, the rheological behavior will be different depending on the fiber type. In addition, the viscosity and elastic modulus increase with the nanofiber concentration even if the starting material is the same (Charani et al 2013;Iotti et al 2011;Pääkkö et al 2007;Yamagata et al 2020).…”
mentioning
confidence: 99%